Diplomával a munka világában – a túlképzettség okai = Graduated workers - reasons for overducation - Kotsis, Ágnes (Közép-Európai Közlemények, 2017)
After the changes in the economic and political system, between 1990 and 2010 the number of students in tertiary education increased about three and half times: the number of full-time students is three times greater, while the number of correspondence students is five times greater than it was around the time of the system change. While in 1999 the 19-year old cohort enrolment rate was 21%, and the 20 year-old cohort enrolment rate was 24%; in 2007 these percentages were 34% and 38% according to OECD database. Thus we are close to ‘mass higher education’. Until 2012 this rate did nőt change, it started to decrease a little bit only affér 2012. So a question arises: how does it influence the employment attributes of graduated students. It may happen that the graduate students will not find a job that match to their education level and thus they become overeducated. In this case according to the Hungárián and intemational research, their wage prémium is lower than their counterparts in a ‘proper’ job. In this research I examine what kind of factors increase the probability of being an overeducated graduate, and finally I test them on the database of University of Debrecen.